A Riboswitch-Driven Era of New Antibacterials - Nikoleta Giarimoglou; Adamantia Kouvela; Alexandros Maniatis; Athanasios Papakyriakou; Jinwei Zhang; Vassiliki Stamatopoulou; Constantinos Stathopoulos (MDPI AG, 2022)
Riboswitches are structured non-coding RNAs found in the 5' UTR of important genes for bacterial metabolism, virulence and survival. Upon the binding of specific ligands that can vary from simple ions to complex molecules such as nucleotides and tRNAs, riboswitches change their local and global mRNA conformations to affect downstream transcription or translation. Due to their dynamic nature and central regulatory role in bacterial metabolism, riboswitches have been exploited as novel RNA-based targets for the development of new generation antibacterials that can overcome drug-resistance problems. During recent years, several important riboswitch structures from many bacterial representatives, including several prominent human pathogens, have shown that riboswitches are ideal RNA targets for new compounds that can interfere with their structure and function, exhibiting much reduced resistance over time. Most interestingly, mainstream antibiotics that target the ribosome have been shown to effectively modulate the regulatory behavior and capacity of several riboswitches, both in vivo and in vitro, emphasizing the need for more in-depth studies and biological evaluation of new antibiotics. Herein, we summarize the currently known compounds that target several main riboswitches and discuss the role of mainstream antibiotics as modulators of T-box riboswitches, in the dawn of an era of novel inhibitors that target important bacterial regulatory RNAs.